2014
DOI: 10.4314/tjpr.v13i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of Insulin-Chitosan Nanoparticles

Abstract: Purpose: To optimize the preparation of insulin-chitosan nanoparticles (ICNS) using response surface methodology (RSM). Methods: ICNS were formulated through ionic cross linking method. The effects of the ratio between insulin and chitosan, pH of the medium and rotation speed on insulin encapsulation efficiency (EE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Studies [25,26] have indicated that RSM is an outstanding and effective statistical technique for complex optimization processes by reducing the number of experimental trials compared with traditional methods. Thus, it is widely used to optimize the extraction process of polysaccharides [27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies [25,26] have indicated that RSM is an outstanding and effective statistical technique for complex optimization processes by reducing the number of experimental trials compared with traditional methods. Thus, it is widely used to optimize the extraction process of polysaccharides [27].…”
Section: Discussionmentioning
confidence: 99%
“…(NaOH) (Hecq et al, 2015;Li et al, 2017), or insulin can even be directly solubilized into diluted NaOH, or directly into TPP solution (Zhao et al, 2014). Then, the insulin solution is added to the chitosan solution right before or during TPP addition (Ma et al, 2005;Azevedo et al, 2011;Makhlof et al, 2011) or added after TPP addition to chitosan (Ma et al, 2002;Erel et al, 2016).…”
Section: Drug Encapsulation Intomentioning
confidence: 99%
“…There are many different protocols for insulin encapsulation into Chit NPs (Figure 2). Insulin can be pre-dissolved in diluted hydrogen chloride (HCl) solution (Abbad et al, 2015), the pH of this final solution can be adjusted with sodium hydroxide (NaOH) (Hecq et al, 2015;, or insulin can even be directly solubilized into diluted NaOH, or directly into TPP solution (Zhao et al, 2014). Then, the insulin solution is added to the chitosan solution right before or during TPP addition (Ma et al, 2005;Azevedo et al, 2011;Makhlof et al, 2011) or added after TPP addition to chitosan (Ma et al, 2002;Erel et al, 2016).…”
Section: Drug Encapsulationmentioning
confidence: 99%